Infrastructure as an asset class - Georg Inderst (EIB Papers, 2010)
Infrastructure as a new asset class is said to have several distinct and attractive investment characteristics. This article reviews concepts, market developments and empirical evidence on the riskreturn and cash flow profile, and the potential for diversification and inflation protection in investor portfolios. Furthermore, a new, global analysis of the historical performance of infrastructure funds is undertaken. There is no proper financial theory to back the proposition of infrastructure as a separate asset class. Infrastructure assets are very heterogeneous, and empirical evidence suggests an alternative proposition that treats infrastructure simply as a subasset class, or particular sectors, within the conventional financing vehicle on which it comes (e.g. listed and private equity, bonds).
Keywords: 330